Hubungan Tuntutan Kerja dan Sumber Daya terhadap Stres Kerja di Sektor Pelayanan Kesehatan : Systematic Review - Emi Latifah; Zahroh Shahuliyah; Cahya Tri Purnami (Universitas Pahlawan Tuanku Tambusai, 2026)
Background Healthcare workers are required to provide fast, accurate, and empathetic services, often under limited resources. The imbalance between high job demands and insufficient resources increases the risk of stress, burnout, and reduced service quality. Objective To examine the relationship between job demands and resources on work stress among healthcare workers. Method A systematic review using the PRISMA Framework was conducted on 13 national and international articles published between 2021–2025 that focused on job demands and resources in relation to work stress in the healthcare sector. Results Job demands such as physical workload, administrative tasks, emotional burden, and time pressure were found to increase stress, while resources including social support, supportive leadership, organizational policies, adequate facilities, and personal resources played a protective role. Conclusion The balance between job demands and resources determines the level of stress among healthcare workers. Integrated workload management strategies combined with strengthening organizational and personal resources are essential to maintain healthcare workers’ well-being and service quality. Keywords: Work stress, healthcare workers, job demands